Application of Accounting Information Systems at Zakat, Infaq, Sadaqah Institutions in an Effort to Improve Internal Control on Cash Receipts: Penerapan Sistem Informasi Akuntansi Pada Lembaga Zakat, Infaq, Shadaqah Dalam Upaya Peningkatan Pengendalian Internal Pada Penerimaan Kas - Miftachul Hanifa; Fityan Izza Noor Abidin (Academia Open, 2021)
This study aims to determine the application of accounting information systems at zakat, infaq, shadaqah institutions in an effort to improve internal control on cash receipts at LAZISMU Sidoarjo. This research approach uses a qualitative approach with primary data sources. Data collection was obtained from the results of interviews, observations and documentation. Technical validity of data with triangulation model. The results of the study stated that the application of the accounting information system at LAZISMU, Sidoarjo Regency had used a system from the center, namely the ZISKA software which stands for (Zakat, Infaq, Shadaqah, and Humanity). The advantages of the system are more detailed. However, there are obstacles that occur such as network disturbances and to prevent the risk of data loss, data backup is carried out. To anticipate errors in recording cash receipts, cross checks and evaluations are carried out through meetings. The use of the form or document has been serially numbered printed. Transparent financial reports to the public. Cash deposits to the bank are made every day and are directly deposited on bank business days. In the element of internal control, several weaknesses were found.